Radicalism, Revolution, and Reform in Modern China: Essays in Honor of Maurice Meisner - Lynch, Catherine; Marks, Robert B.; Pickowicz, Paul G. (Lexington Books, 2011)
This volume illuminates the relationship of China's radical past to its reformist present as China makes a way forward through very differently conceived and contested visions of the future. In the context of early twenty-first century problems and the failures of global capitalism, is China's history of revolutionary socialism an aberration that is soon to be forgotten, or can it serve as a resource for creating a more fully human and radically democratic China with implications for all of us? Ranging from the early years of China's revolutionary twentieth-century to the present, the essays collected here look at the past and present of China with a view toward better understanding the ideas, ideals, and people who have dared to imagine radical transformation of their worlds and to assess the conceptual, political, and social limitations of these visions and their implementations. The volume's chapters focus on these issues from a range of vantage points, representing a spectrum of current scholarship. The first half of the book brings new insights to understanding how early-twentieth century intellectuals interpreted ideas that allowed them to break with China's past and to envision new paths to a modern future. It treats of Chen Duxiu, a founder of the Communist party, Mao Zedong, and Mao in relation to the non-Communist Liang Shuming and with the Dalai Lama. With continuing threads of nation and nationalities, of peasants, utopias and dystopias linking the chapters, the book's second half looks broadly at the consequences of the implementations of radical ideas, at the same time critiquing our accepted frameworks of analysis. Moving up to the present, the book investigates the effects of the reforms since the 1980s on long-term environmental degradation and on the emergence of a capitalist rural economy. It gives an unsparing view into contemporary rural China through independent films. The book concludes with an analysis of the unshakable persistence of the shibboleth, 'the rise of China,' in popular and academic imagination and argues for the importance instead of taking seriously the twentieth-century history of radicalism in China and its significance for understanding China's present and its future potentials.